Implementación del sistema contable en la empresa farmacéutica “Tu Farmacia” de la ciudad de Santo Domingo periodo octubre del 2013 - Cueva Carrión, Carmen Mercedes (2015)
The “IMPLEMENTATION OF ACCOUNTING SYSTEM IN PHARMACEUTICAL COMPANY " YOUR PHARMACY" OF THE CITY OF SANTO DOMINGO PERIOD OCTOBER 2013”, due to the requirement of the National University of Loja, through its rules for obtaining professional title, allowing practice the knowledge acquired in the race accounting and auditing. The social problem under study is a reality, which was investigated to give timely, reaffirming knowledge and providing the same for better economic development, through the classification of information, preparation of plan and manual accounts, auxiliary and main, the inventory, namely the development of accounting practice to obtain financial statements, which revealed the real economic situation being experienced by the company, while contributing to the University, students and the general public as a means of relevant inquiry to feedback their knowledge. Registration of inventory allowed to know the real stock with which account, important as it is necessary to continue carrying this system for adequate control of the products you own as well as those who need to supply advance weather its clientele. The application of the accounting process allowed the company a clear picture of their economic situation - financial, so it is recommended that you continue to make this process easier knowing that their economic reality allowing the right decisions for their future development